Upaya Guru BK Melalui Teknik Self-Management untuk Meningkatkan Kematangan Karir Siswa SMK Ma’arif NU 1 Cilongok - Fahmi Fahrezi, Fahmi; Wisnuaji, Aditya; Budiyono, Alief; Nurrahman, Yudha Faki (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the role of Guidance and Counseling teachers in enhancing career maturity among 12th-grade students at SMK Ma'arif NU 1 Cilongok through the implementation of Self-Management techniques. This research employs a descriptive qualitative approach with subjects consisting of vocational school students and Guidance and Counseling (BK) teachers. Data was collected through interviews, observations, and documentation, then analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The results indicate that Self-Management techniques, which include self-monitoring, self-reward, and stimulus control, are effective in enhancing students' awareness and abilities in career planning. The guidance program designed by the BK teachers helps students understand their potential, set realistic career goals, and take concrete steps toward their future. These findings highlight the importance of self-management training for students and the need for BK teachers' support in guiding them to achieve optimal career maturity. The implementation of these techniques is recommended to be integrated into the school curriculum with collaborative support from parents and industry stakeholders.